O trono vazio: a teoria unitária do poder na genealogia teológica de Giorgio Agamben - Pereira, Pedro Lucas Dulci (2015)
The present dissertation aims to explore only one of the input ports of the philosophy of Giorgio Agamben: the theological genealogy signature "power" in its unitary form. Despite the multifaceted work of Agamben, there is a kind of spine that runs through all the philosopher's reasoning in the last 25 years. Agamben usually puts his reader that place he calls the zone of indifference, or even of inoperativity. The origin of the idea of a zone of indifference or inoperativity that Agamben uses as ubiquitous assumption in his work, is precisely the Judeo-Christian messianic theology - so it is a theological genealogy. This philosophy of indifference or political messianism present in the work of Agamben always shown from three basic movements operated by the author. First, he criticizes between two categories historically placed in opposition in Western thought. Zoe and bios, inside and out, law and anomy, exception and rule, etc. After highlighting this polarity, it passes to the second movement that comes to bring out an indifference zone between these two poles. The figure of the homo sacer, the state of emergency, the concentration camp, etc., are also examples of people, places and situations where these bilateral oppositions become indifferent and enter a inoperativity zone. All this he shows that, finally, in the third movement of his argument, be able to present what is perhaps a unique proposition: the messianic moment of destituinte suspension. The Franciscan way of life, the use without possession, divine violence, or profanity are different ways of bringing an action that is outside the reading key metaphysical power / act. Each of these fundamental movements will be explored in the three parts of this dissertation focusing mainly on the signature “power” in his philosophy.